Fall down 7 times get up 8 : a young man's voice from the silence of autism - Higashida, Naoki, 1992- (Random House, 2017)
"The author of the bestselling phenomenon The Reason I Jump returns with a unique memoir about life as a young adult with severe autism. With an introduction by David Mitchell, who translated this book with his wife, KA Yoshida, this extraordinary new work explores education, identity, family, society, and personal growth, opening a window into the mind of its nonverbal author and providing remarkable insights into autism in general"--